Proposal of a methodology to use offshore wind energy on the southeast coast of Brazil - Gomes, Mateus Sant’Anna de Sousa (2019)
The electric energy matrix in Brazil mostly comprises energy from hydroelectric power plants, approximately 60.8%. This large participation presents some vulnerability in periods of drought and often the country’s electric energy matrix is complemented by the use of other energy sources, such as thermoelectric. Even though it is currently among the largest onshore wind power producers in the world, Brazil has not yet started developing this energy source in the offshore segment. However, this study shows that offshore wind energy can be a complementary energy source for the country’s electric energy matrix, and thus replace other energy sources which have more impact on the environment. Therefore, this study sought to develop a methodology that can be easily replicated using free access tools, aiming to contribute to the development of offshore wind technology and future research in the country. The results show a large production of offshore wind energy in the southeastern region of Brazil. The "Cabo Frio 2″ data collection point presented the highest annual production of offshore wind energy. However the study opted for the "Arraial do Cabo-A606″ collection point located in the state of Rio de Janeiro and at ocean depths that can be reached by fixed foundations